Boosting the OER activity of amorphous IrOx in acidic medium by tuning its electron structure using lanthanum salt nanosheets. (12th January 2023) - Wang, Xuefeng; Jang, Haeseong; Li, Zijian; Li, Haisen; Li, Guangkai; Kim, Min Gyu; Ji, Xuqiang; Qin, Qing; Liu, Xien
Abstract : The interaction between Ir and La via O atoms as a bridge in a-IrO x /LaCO3 OH boosts the acidic OER activity of a-IrO x . Abstract : Promoting the activity of Ir-based nanomaterials for oxygen evolution reaction (OER) in acid media without losing their durability is crucial for reducing overpotentials in energy conversion, such as electrochemical water splitting. Here, a nanocomposite composed of a-IrO x and lanthanum salt (LaCO3 OH) was constructed to further improve its OER activity by tuning the electronic structure of a-IrO x, because a-IrO x is a well-known critical material as the active layer of Ir-based anodic catalysts. The interaction between Ir and La via O atoms as a bridge in the catalyst IrO x /LaCO3 OH, verified by X-ray absorption near edge structure spectroscopy, tunes the electronic structure of a-IrO x and thus obviously enhances its activity for the OER in acid media, compared with commercially available IrO2 as well as most of the reported Ir-based OER electrocatalysts. The overpotential of IrO x /LaCO3 OH at a current density of 10 mA cm −2 is 255 mV with a Tafel slope of 55 mV dec −1 . This work reveals that the strong electronic interaction between Ir- and La-based materials can efficiently improve activity and reduce energy consumption, as well as enlarging the family of acidic OER electrocatalysts.